LX design with food - Marat-Mendes, T. (Experiencing Food: Designing Dialogues: Proceedings of the 1st International Conference on Food Design and Food Studies (EFOOD 2017), Lisbon, Portugal, October 19-21, 2017, 2018)
This paper exposes the results of an academic experience which informs how the food system can be reinforced in architectural higher education, while providing: (1) a better relation of the urban realm to the food thematic; (2) perceive the impact of urban form on the food system, in space and time; and (3) promote design solutions for a more resilient, socially inclusive and sustainable city, as recently proposed by the Urban Food Policy, signed by several European municipalities.